2023
DOI: 10.3389/fpls.2023.1061663
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modulation of Valencia sweet orange field performance by 50 rootstocks under huanglongbing-endemic conditions

Abstract: Although the citrus scion cultivar primarily determines the characteristics of the fruit, the rootstock cultivar of the graft combination has a major role in determining the horticultural performance of the tree. The disease huanglongbing (HLB) is particularly devastating to citrus, and the rootstock has been demonstrated to modulate tree tolerance. However, no existing rootstock is entirely suitable in the HLB-endemic environment, and citrus rootstocks are particularly challenging to breed because of a long l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Although many Poncirus hybrids produce juice with a bitter flavor and aftertaste, a recent investigation identified four hybrids resulting from crosses between Citrus and P. trifoliata with a favorable taste (Deterre et al 2023). Microcitrus species have also been used in rootstock and scion breeding programs, partly because of their tolerance against HLB (Bowman et al 2023;Ramadugu et al 2016). However, Microcitrus hybrids generally have not performed well as rootstocks (Bowman et al 2023), and their fruits are generally unsuitable for juicing or fresh consumption (Bowman et al 2019;Shaw et al 2000), likely requiring several generations of backcrossing to obtain suitable fruit quality in progeny for use as a commercial scion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many Poncirus hybrids produce juice with a bitter flavor and aftertaste, a recent investigation identified four hybrids resulting from crosses between Citrus and P. trifoliata with a favorable taste (Deterre et al 2023). Microcitrus species have also been used in rootstock and scion breeding programs, partly because of their tolerance against HLB (Bowman et al 2023;Ramadugu et al 2016). However, Microcitrus hybrids generally have not performed well as rootstocks (Bowman et al 2023), and their fruits are generally unsuitable for juicing or fresh consumption (Bowman et al 2019;Shaw et al 2000), likely requiring several generations of backcrossing to obtain suitable fruit quality in progeny for use as a commercial scion.…”
Section: Discussionmentioning
confidence: 99%
“…Foliar symptoms. Blotchy mottle and nutrient deficiency-like symptoms were scored in each canopy quadrant using a 5-point standard scale as previously described (Bowman et al 2023). Blotchy mottle was scored as follows: 1 5 no blotchy mottle; 2 5 less than 25% of leaves with blotchy mottle; 3 5 26% to 50% of leaves with blotchy mottle; 4 5 51% to 75% of leaves with blotchy mottle; and 5 5 more than 75% of leaves with blotchy mottle.…”
Section: Canopy Health Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Swingle and standard sour orange are two of the most common rootstocks used in Florida. A detailed report of rootstock performance during this trial was published (Bowman et al 2023). Overall tree survival through 2021 was 94%, and tree testing by reverse-transcription polymerase chain reaction revealed that 100% of the trees were infected by CLas and 90% were infected by citrus tristeza virus.…”
Section: Field Performancementioning
confidence: 99%
“…The four hybrid rootstock selections originated from crosses made at the USDA A.H. Whitmore Foundation Farm by Kim Bowman between 2000 and 2006, and each has distinctly different parentage (Table 1). These hybrids are the product of a new USDA citrus rootstock breeding strategy, termed SuperSour, that has been previously described (Bowman and Joubert 2020;Bowman et al , 2023. Generally, the SuperSour strategy uses a broad range of parental material that includes either standard sour orange itself (C. aurantium) or some combination of the parental species that gave rise to standard sour orange, the mandarin (C. reticulata), and pummelo (C. maxima).…”
Section: Originmentioning
confidence: 99%